A new secoiridoid glycoside and a new sesquiterpenoid glycoside from Valeriana jatamansi with neuroprotective activity. (September 2016) - Tan, Yu-Zhu; Yong, Yan; Dong, Yan-Hong; Wang, Ru-Jing; Li, Hong-Xiang; Zhang, Hai; Guo, Da-Le; Zhang, Shi-Jin; Dong, Xiao-Ping; Xie, Xiao-Fang
Graphical abstract: Highlights: ⿢ Ten iridoids and one sesquiterpenoid glycoside were studied from the roots of Valeriana jatamansi . ⿢ Phytochemical investigations led to the isolation of a new secoiridoid glycoside (1 ) and a new sesquiterpenoid glycoside (2 ). ⿢ All the compounds were assayed for neuroprotective activity. Abstract: A new secoiridoid glycoside, isopatrinioside (1 ) and a new sesquiterpenoid glycoside, valeriananoid F (2 ), together with nine known compounds, were isolated from the roots of Valeriana jatamansi . Their structures were elucidated on the basis of spectroscopic analysis. Compound1 was an unusual monocyclic iridoid glycoside ring-opened between C-1 and C-2 produced by the cleavage of the pyran ring. Of the eleven isolates, compounds1 and4 exhibited moderate neuroprotective effects against CoCl2 -induced neuronal cell death in PC12 cells.